Evaluating the Quality of Website Information of Private-Practice Clinics Offering Cell Therapies in Japan - Kashihara, Hidenori (Interact J Med Res, 2016)
BACKGROUND: Although the safety and effectiveness of stem cell therapies are yet to be proven, recent studies show that such therapies are being advertised with some questionable marketing techniques to effect positive portrayal of the therapies on the webpages of private-practice clinics to sell their therapies worldwide. In such context, those clinics communicate directly with consumers (patients and their family members) via the clinics’ websites. Meanwhile, the Health Science Council at the Ministry of Health, Labour, and Welfare (MHLW) in Japan has pointed out noncompliance of some local clinics with the provisions concerning medical advertising in the Medical Care Act in the past. However, locally little is known about the current status of those clinics including the quality of their webpage information disseminated. OBJECTIVE: To evaluate the quality of website information of private-practice clinics offering cell therapies in Japan. METHODS: Twenty-four websites with 77 treatments from the Google search were identified for evaluation. The following three exploratory analyses were performed: first in order to ascertain web-based portrayal of private-practice clinics offering cell therapies, a descriptive analysis was conducted using a coding frame; second we evaluated the quality of the target website information from the viewpoint of the level of consideration taken for patients and their family members, using 10 quality criteria (“the Minimum Standard”) from the e-Health Code of Ethics 2.0; third we counted and coded expressions that matched set categories for “name-dropping” and “personalized medicine” in the information posted on these websites. RESULTS: Analysis on the treatments (N=77) revealed 126 indications (multiple response): the top three indications were “cancer,” “skin-rejuvenation/antiaging/anti–skin aging,” and “breast augmentation/buttock augmentation.” As for the portrayal of treatment risks and benefits, 78% (60/77) of treatments were mentioned with “benefits,” whereas 77% (59/77) of treatments were mentioned with “risks.” As for the source(s) cited for the discussions of treatment risks and benefits, no treatment quoted an expert’s opinion for the risks, whereas 7% (6/77) treatments quoted external sources for the benefits. As for the results with e-Health Code of Ethics 2.0, not a single clinic fulfilled all the 10 criteria; 63% (15/24) of the clinics was found exercising “name-dropping,” and 21% (5/24) of the clinics mentioned expressions related to “personalized medicine” on their websites. CONCLUSIONS: Our website content analyses confirmed the following: (1) the clinics mentioned the risks or benefits of the treatments with hardly any scientific citations, (2) the way the website information was disseminated was inappropriate for patients and their families, and (3) many websites seemed to be using marketing techniques in order to draw patients’ interests or attentions. It is important that more similar studies are undertaken globally to enable an orchestrated regulatory approach toward private-practice clinics.